The Investigating Tactile Experiences and Textures with Sustainable Materials in Art and Design Education - Lin, Lung-Chi; Vongphantuset , Jirawat; Sirivesmas, Veerawat (Journal of Roi Kaensarn Academi, 2024)
This research investigates how tactile experiences with sustainable materials influence educational outcomes, emphasizing how interacting with these materials can enhance students’ creativity, learning experiences, and increase awareness of sustainability. Traditional discussions have focused on the environmental benefits of these materials, often neglecting their educational and experiential value. This study aims: (1) to explore tactile experiences with various sustainable materials; (2) to examine these materials through experiential learning practices; and (3) to measure students’ agreement using a questionnaire on tactile experiences with sustainable materials in educational settings, thereby promoting a participatory and tactile-focused learning approach. This study employed a mixed-methods approach, including in-depth interviews with three art and design experts, three participatory workshops, and questionnaires to collect data. The research involved 48 student participants in three participatory workshops, enabling an analysis of their tactile interactions with sustainable materials. In the results, descriptive analysis showed the significant role of textures in enhancing the appeal of tactile experiences and the impact of sustainable materials on these experiences, thereby enriching educational engagement. The majority of student participants recognized the value of using sustainable materials in art and design education, indicating a better understanding and awareness. However, students’ application of sustainable materials to art projects was limited. In conclusion, the study highlights the educational and experiential value of tactile interactions with sustainable materials in art and design education. Integrating these materials can increase tactile experiences, sustainability awareness, and students’ engagement. This research addresses the gap in the existing literature and recommends conducting further research and assessment of practical applications in the field.